Human sexuality : from cells to society - Rosenthal, Martha S. (Australia : Wadsworth, Cengage Learning, 2013)
Using humor and a contemporary voice, HUMAN SEXUALITY FROM CELLS TO SOCIETY, 1E engages readers to acquire a greater knowledge of their bodies, their values, and their relationships with others. This concise, comprehensive, and up-to-date book emphasizes critical thinking--in both human sexuality research as well as readers' own sexual lives--and is geared to help readers understand the diverse foundations of sexuality, as well as provide skills to evaluate current research and data. Working from a multidisciplinary perspective, the author's approach is accessible to anyone, even without a background in biology or critical thinking, and allows readers to see how human sexuality interrelates with psychology, biology, health, law, media, religion, and other topics that at first glance seem unrelated.
Introduction to sexuality -- Evaluating studies of sexuality -- Male reproductive anatomy and physiology -- Female reproductive anatomy and physiology -- Sex and gender -- Sexual response -- Attraction, dating, and hooking up -- Love -- Committed relationships and communicating with your partner -- Sexual orientation -- Consensual sexual behavior -- Contraceptive choices and ending pregnancy -- Conception, pregnancy, and birth -- Sexually transmitted infections -- Variations in sexual behavior -- Sexual coercion and violence -- Sex for sale.
Includes bibliographical references and index.
Keywords: SEX INSTRUCTION